A Particle of Amazement Which Will Become the Essence of Eternity. The Meaning of Friendship in the Life and Thought of Saint John Paul II - Filip De Rycke (Polonia Sacra)
Friendships with the most various kinds of people played an important role in the life of Saint John Paul II. In his reflections on friendship, the pope elaborates Thomistic categories from his personalist perspective. According to Pope Wojtyła, friendship is a specific form of chaste love. Among the friends, it works out a deep union that is an image of the triune God and an anticipation of the everlasting communion of the saints.